Dyslexia and neuroscience : the Geschwind-Galaburda hypothesis 30 years later - Gaab, Nadine; Hoeft, Fumiko; McCardle, Peggy (Baltimore : Paul H. Brookes Publishing Co., 2018)
'Thirty years ago, the groundbreaking Geschwind-Galaburda hypothesis defined the field of dyslexia, revealing and analyzing the complex associations among brain development, hormones, immune activity, and brain lateralization. This important volume revisits the hypothesis three decades later and explores key questions: What have we learned since then, and what still needs to be investigated? Based on presentations from the 2016 Extraordinary Brain Symposium-and co-edited by one of the authors of the original hypothesis-this book synthesizes current dyslexia findings from more than 30 top researchers and practitioners. The contributors share diverse perspectives, concerns, challenges, and solutions, with brief jargon-free summaries at the beginning of each chapter to make the book accessible to a wider audience. Each chapter also points to research gaps and remaining questions to help shape future innovations from the next generation of researchers. A landmark addition to the literature on dyslexia and neuroscience, this forward-thinking volume should be on the shelf of every researcher and graduate student whose work focuses on neuroscience and dyslexia. EXPLORE CURRENT FINDINGS ON the clinical and sociological aspects of dyslexia early atypical brain development in developmental dyslexia reading in children with developmental disorders brain asymmetries and sex differences in developmental dyslexia sex differences in cognition and learning intergenerational transmission of reading and reading brain networks animal models of early neural disruption the genetic factors that underlie handedness and left hemisphere language dominance the genetics of specific reading disability and more essential dyslexia topics With contributions by David Urion John L.R. Rubenstein Gert J. de Vries Thomas G. O'Connor Tuong-Vi Nguyen Margaret M. McCarthy Franck Ramus Eileen Luders David S. Hong R. Holly Fitch Laurie Cutting Elena Grigorenko Sebastian Ocklenburg Silvia Paracchini Sergey Kornilov Heidi Feldman Nicole Landi and more'--
'This 15th volume in the Extraordinary Brain Series is focused on research in dyslexia and neuroscience in response to the Geschwind-Galabura hypothesis that defined the field of dyslexia 30 years ago. In the 1980s, Norman Geschwind and Peter Behan reported increased prevalence of left-handedness and autoimmune disorders in individuals and families with developmental dyslexia. Following this report, Geschwind, in collaboration with Albert Galaburda, wrote a paper in the Archives of Neurology discussing developmentally relevant associations between brain development, hormones, immune activity, and brain lateralization, which resulted in human diversity in talents and disabilities. There have been many technological advances in laboratory science, neuroimaging, genetics, and behavioral science in the last 30 years. Still, many of the questions and issues raised in this landmark paper have not been definitively addressed. Invited attendees of the 2016 Extraordinary Brain Symposium (hosted by The Dyslexia Foundation) revisited the hypothesis and assessed what remains to be investigated; this book is based on the attendees' Symposium presentations'--
Includes bibliographical references and index.
Keywords: Dyslexia -- Research; Brain -- Diseases -- Research